Efficient One‐Pot Synthesis of 3, 5‐Disubstituted 1, 3, 4‐Thiadiazole from Dithioesters under Mild Condition. Issue 15 (23rd April 2019) - Kemparajegowda,; Swarup, Hassan A.; Sandhya, Nagarakere C.; Rangappa, Shobith; Mantelingu, Kempegowda; Rangappa, Kanchugarakoppal S.
Abstract: An efficient synthetic approach for the construction of 3, 5‐disubstituted 1, 3, 4‐thiadiazoles from dithioesters, hydrazine hydrate and triethyl amine has been developed under transition‐metal free condition. This methodology efficiently constructs 3, 5‐disubstituted 1, 3, 4‐thiadiazole in good to excellent yields with the advantages of wide functional group tolerance and operational simplicity. Abstract : Construction of 3, 5‐disubstituted 1, 3, 4‐thiadiazole using highly reactive species‐dithioesters under mild condition through intramolecular cyclization reaction. This approach is compatible for the preparation of larger‐scale synthesis of 3, 5‐disubstituted 1, 3, 4‐thiadiazole derivatives.